Formal Verification of CHAP PPP authentication Protocol for Smart City/Safe City Applications. Issue 1 (1st January 2022) - Pradeep, R; Sunitha, N R
Abstract: A smart city is a technologically advanced metropolitan region with several connected devices that collects data using various electronic technologies, voice activation methods, and sensors. The information obtained from the data is utilised to efficiently manage assets, resources, and services; in turn, the data is used to enhance operations throughout the city. Achieving security for smart cities is one of the major challenges as the number of connected devices increases the vulnerability also increases. The security of a smart city system depends on the reliability of the security protocols used by the security systems. To design and develop a highly secure system for a smart city the security protocols used must be highly reliable. To prove the reliability of a security protocol the validation technique is not desirable because of its several drawbacks, these drawbacks can be overcome using the formal verification technique which provides the mathematical proof for its correctness. In this work, The Challenge-Handshake Authentication Protocol Point-to-Point (CHAP PPP) which is more commonly used in PPP authentication of smart cities is formally verified using the well-known verification technique known as the model checking technique. The Scyther model checker is the tool used to build the abstract security protocol model.